The Role of Digital Leadership and Administrative Innovation in Enhancing School Management Effectiveness in the Era of Education 5.0 - M Karim; Karlini Oktarina; Syafrul Antoni (AKADEMI TEKNIK ADI KARYA, 2025)
Abstract This study aims to analyze the role of digital leadership and administrative innovation in improving school management effectiveness within the framework of Education 5.0. Employing a literature review method, this research synthesizes relevant empirical studies, theoretical frameworks, and recent scholarly discussions from international journals published between 2018 and 2025. The review explores how digital leadership competencies such as data-driven decision-making, digital ethics, and adaptive communication contribute to the development of innovative administrative practices in schools. Findings indicate that digital leadership fosters a culture of continuous improvement, enhances collaboration through digital platforms, and promotes organizational agility in response to technological disruptions. Furthermore, administrative innovation serves as a mediating factor that transforms leadership vision into operational effectiveness by streamlining processes, optimizing resource management, and increasing stakeholder engagement. In the context of Education 5.0, where human-centric and technology-integrated approaches dominate, both digital leadership and administrative innovation are pivotal in ensuring sustainable educational governance. The study concludes that strengthening the digital capacity of school administrators and integrating innovation-driven administrative systems are key strategies for achieving effective and future-ready school management.